Conidia production of Beauveria sp. by solid-state fermentation for biocontrol of Ilex paraguariensis caterpillars - Dalla Santa, H S; Sousa, N J; Brand, D; Dalla Santa, O R; Pandey, A; Sobotka, M; Paca, J; Soccol, C R (Folia microbiologica, 2004)
Conidia production of Beauveria sp. strain LAG by solid-state fermentation (SSF) using blends of agro-industrial residues (residual potatoes and sugar-cane bagasse) was optimized with respect to cultivation conditions and the composition of substrate mixture in Erlenmeyer flasks and column-type bioreactor. With a blend of 60 % residual potatoes and 40 % sugar-cane bagasse the optimum conditions achieved were: incubation temperature 26 degrees C, initial substrate pH 6, inoculum concentration 10(7) conidia per g substrate; optimal initial moisture of the substrate was 70 % for Erlenmeyer flasks, in column-type bioreactor (with forced aeration) the optimal initial moisture of the substrate was 65 % with airflow of 60 mL/min. The highest production (1.07 x 10(10) conidia per g dry substrate) was achieved after a 10-d fermentation. The conidia were used in laboratory assays against Thelosia camina and Hylesia sp., caterpillars that are serious pests of mate plants. The mortality of T. camina was >90 % 10 d after spraying caterpillars with 1 mL conidia suspension at a concentration 10(5)-10(8)/mL. For Hylesia sp., the mortality was 70 %, 7 d after immersion in the conidia suspension containing 108 conidia per mL. Therefore, the Beauveria sp. LAG can be considered to be an important biocontrol instrument in the prospect of the Integrated Pest Management for mate plants.
Keywords: Pest Control, Biological; Mitosporic Fungi; biologická kontrola škůdců; Fermentation; Animals; fermentace; motýli; Ilex paraguariensis; Butterflies; mitosporické houby; zvířata